Groundwater Exploitation on the High Plains - Kromm, David E.; Kromm, David E. (Book collections on Project MUSE., 1992)
The High Plains region was once called the Great American Desert and thought to be, in the words of explorer Stephen Long, "wholly unfit for cultivation."Now we know that beneath the surface, unbeknownst to the explorers and early settlers, lies the Ogallala aquifer, an underground formation that stretches for 800 miles from the Texas panhandle to South Dakota. It holds more water than Lake Huron. Indeed, the Ogallala has been referred to as the sixth Great Lake. It is the water pumped for irrigation from the Ogallala that has enabled a naturally dry region to produce up to 40 percent of America's beef and 20 to 25 percent of its food and fiber, an output worth about $20 billion.In the forty years since the invention of center pivot irrigation, the High Plains aquifer system has been depleted at an astonishing rate. In 1978 the volume of water pumped from the aquifer exceeded the annual flow of the Colorado River. In Texas, water levels are down 200 feet in some areas. In Kansas, 700 miles of rivers that once flowed year round no longer flow at all. In short, the High Plains may be becoming the desert it was once thought to be. Is it too late to solve the problem?Geographers David Kromm and Stephen White assembled nine of the most knowledgeable scholars and water professionals in the Great Plains to help answer that question. The result is a collection of essays that insightfully examine the dilemmas of groundwater use. From a variety of perspectives they address both the technical problems and the politics of water management to provide a badly needed analysis of the implications of largescale irrigation. They have included three case studies: the Nebraska Sand Hills, Northwestern Kansas, and West Texas. Kromm and White provide an introduction and conclusion to the volume.